Reliability analysis & performance-based code calibration for slabs/walls of protective structures subject to air blast loading - Bhuyan, Kasturi; Sharma, Hrishikesh (Reliability engineering & system safety, 2022)
•A performance-based design (PBD) framework for Normal Strength Concrete (NRC) & Ultra-High Strength Concrete (UHSC) panel subjected to air blast loading is developed.•Fragility estimation is done to show the credibility of models.•Developed Load & Resistance factors circumvent the existing limitations of the current code provisions.•Hazard curves are developed for mass and stand-off distance from available literature.•The total probability of failure is estimated for the panels to check for the overall vulnerability of the structure. A multilevel performance-based design (PBD) framework is developed for panels of Protective structures subjected to air blast. These provisions improve the existing design approach of blast resistance structures for ultimate limit state. Present study develops probabilistic deflection-based capacity and demand models for three performance levels associated with four damage states occurring during an air blast. The chosen protective structures for current study are reinforced Normal Strength Concrete (NRC) and reinforced Ultra-High Strength Concrete (UHSC) panels. The probabilistic models are developed using Bayesian inference (Posterior Statistics). The database is generated through numerical experimental design using finite element (FE) based software, LS-DYNA. The influence of air blast on panel is validated on a panel and obtained results shows the trustworthiness of numerical model. Grounded on these models the fragility estimation is carried out and attained plots demonstrates the consistency. Using a reliability based approach, the Load and Resistance Factors for Design (LRFD) are developed associated with the proposed three performance levels. Hazard curves and total probability are estimated using established dataset from literature available. The estimated LRFD factors can be used for the design of NRC & UHSC panel of slab/walls of protective structure subjected to air blast.